Alimentos consumidos por la ardilla endémica de Perote (Xerospermophilus perotensis) en el Valle de Perote, Veracruz, México - González-Romero, Alberto; Montero-Bagatella, Sandra; Durán-Antonio, Jessica (Instituto de Ecología, A.C., 2018)
The Perote ground squirrel (Xerospermophilus perotensis) is a micro-endemic rodent, classified as an endangered species by the Mexican NOM-059-SEMARNAT-2010 and the IUCN. Studies about this species are scarce, with most of the few published studies addressing its distribution and population monitoring. While the unique previous study on its diet, reports only six plant species. Based on direct observations of food consumption, we recorded in our study 25 plant species and four animal sources of food.